Hardware and software system for assessing operators’ psychophysiological state - Кузовик, Вячеслав Данилович; Гордєєв, Артем Дмитрович (Technology audit and production reserves, 2014)
In today's world there is a need of a high-quality and rapid assessment of psychophysiological state (PPS) of health of operators, engaged in different activities. One of modern methods of assessing psychophysiological state of an operator’s cerebral cortex (CC) is electroencephalography. However, current researches of CC segments, using actual electroencephalographs (EEG), have many disadvantages, which are connected with: the efficiency of using facilities for measuring CC biopotentials and quantitative methods of processing measured data. The software and hardware complex, i.e. an automated expert system, is presented in this paper. It allows a physician to analyze quantitative parameters of stationary records and transient process of the electroencephalogram using the software that, in its turn, allows assessing (diagnosing) operator’s PPSCC. The developed hardware and software system has shown its effectiveness in the process of diagnosing operators’ cerebral cortexes during the experiment stage. The developed software can be used by medical professionals for assessing PPSCC of operators of different activities.